Torsion of a large ovarian cyst presented as an acute abdomen: Case report - Sasho Pucakoski; Nadezda Spiroska; Andrej Nikolovski (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2022)
Patients with acute abdominal pain often end up in the emergency department for surgical treatment. Ovarian cysts can lead to an acute abdomen due to torsion (twisting) or rupture. In this case report we are going to present a 70 y/o female patient with left adnexal torsion, due to a presence of ovarian cyst, presented as an acute abdomen. The patient was enrolled in the emergency department with acute abdomen, nausea and vomiting. After the initial evaluation including a Computerized tomography [CT] scan, the cyst presented as a solid hypodense mass behind the front abdominal wall, with the dimensions of Anteroposterior diameter [APd] 13cm, Laterolateral diameter [LLd] 11cm and Craniocaudal diameter [CCd] 15cm. The possible differential diagnosis [DDx] included cystic tumor [TU] mass on the mesentery as well as a cystic TU on the Urogenital tract (UGT). Intraoperatively adnexal torsion due to an ovarian cyst was found. The cyst and the left adnexa were then removed. Histopathological report showed ovarian hemorrhagic infarction due to a cystic tumor and torsion in the left adnexa. The diagnosis in such cases is often challenging because often the initial CT report can confuse the surgeon whether the mass arises from the mesentery or the urogenital tract.
Keywords: ovarian cyst; adnexal torsion; acute abdomen